PENGARUH SUPLEMENTASI SERAT PSYLLIUM HUSK DAN DIET RENDAH KALORI SEIMBANG TERHADAP KADAR APO B PENYANDANG OBES I - Rozana Nurftri Yulia; Victor Tambunan; Ani Retno Prijanti (ARGIPA (Arsip Gizi dan Pangan), 2016)
ABSTRACTGlobal raising of obesity prevalence nowday had inﬂuence to increasing morbidity andmortality cardiovascular disease (CVD). One of obesity implication is incresing of aterogeniclipid profles such as low-density lipoprotein (LDL). This lipoprotein contains apolipoproteinB (apo B) as hydrophilic agent in circulation. Researches show that level of apo B was betterpredictor of CVD risk factor. The most effective technique in weight loss such as llifestylesinterventions for obese is combining diet and exercise. Current advice is to increase the amountof dietary fber up to 20-35 g/day, for more effective weight loss management. Dietary fber hassignifcant characteristics that affect physiological and metabolic roles including its solubilityin water. Psyllium husk (PH) is a source of natural soluble fber obtained from plantago ovataForssk seed. The aim of this study to investigate the change of apo B level in obese I aftergiven supplementation psyllium husk (PH) 8.4 g/day and low-calorie balanced diet (LCBD)for 4 weeks. We conducted a double blind randomized clinical trial with parallel design.Subjects were randomly allocated into two groups; treatment (T) group and plasebo (P) group.The T subjects received psyllium husk (PH) 8.4 g/day and LCBD 1200 kcal/day and the Psubjects received placebo and LCBD 1200 kcal/day. Data collected in this study consist ofsubject distribution and characteristic, intake of energy, macronutrient, fber, water and apoB level that assessed before and after treatment. Level of statistical analyses signifcance was5%, independent t-test and Mann-Whitney. A total 28 subjects (14 subjects in each group)had completed the intervention. There were no serious adverse events were reported along theintervention. Mean of age in T and P groups respectively was 35.0 (30.0-45.0) years and 34.5(30.0-48.0) years, and BMI was 28.0 ± 1.1kg/m2 and 27.2 ± 1.4 kg/m2. The energy intake in Tgroup 1130.9 ± 221.9 kcal/day was signifcantly higher (p = 0.02) than P group 1024.3 ± 269.9kcal/day. Simple carbohydrate intake in T group (35,6 (8.3-69.9) g/day) was signifcantlyhigher (p<0.0001) than in P group (13.8 (3.4-55.5) g/day). Intake of dietary fber in T groupwas 17.2 ± 2.8 g/day had signifcantly higher than P group 8.2(5.2-15.2) g/day, even addingPH supplementation cannot meet the recommendation of fber intake (20-35 g/day). Decreasingof apo B level in P group was -6.1 ± 8.9 mg/dL that statistically insignifcant difference (p =0.13) with T group -1.3 ± 7.3 mg/dL. We concluded PH supplementation 8.4 g/day and LCBD1200 kcal/day in obese I can not reduce apo B level in 4 weeks.